Essentials of ecology - Miller, G. Tyler (George Tyler) (Thomson Brooks/Cole, 2005)
In this edition, the author has added the "How Would You Vote?" feature, which is an application of environmental science-related topics in the news. Students apply their environmental science knowledge from the book to a Web activity, which helps them investigate environmental science issues in a structured manner